Predictability of clinical outcomes after external beam radiotherapy for hepatocellular carcinoma according to tumor marker dynamics - Park, Sunmin; Rim, Chai Hong; Jung, Young Kul; Yim, Hyung Joon; Chung, Hwan Hoon; Yoon, Won Sup (PloS one, 2025)
Signal changes after high dose irradiation on MRI make it difficult to assess the therapeutic response of hepatocellular carcinoma (HCC). To overcome the limitation of imaging work-up, our study predicted clinical outcomes through tumor marker dynamics in HCC after external beam radiotherapy (EBRT). As a single-center retrospective study, those who underwent conventional fractionated EBRT for viable HCC from 2010 to 2021 were analyzed. Patients with elevated tumor markers of AFP ≥ 10 ng/ml or PIVKA-II ≥ 30 mAU/ml before EBRT were enrolled. Remission of AFP, PIVKA-II, and MoRAL score (=11*√PIVKA-II + 2*√AFP) from pre-EBRT to post-EBRT at 1 month and 3 months was examined. For 1-year and 2-years OS, variables of tumor markers were examined using the receiver operation characteristics (ROC). Multivariate analyses of Cox-regression for OS were conducted. Among 111 patients, 34 patients were estimated to survive more than 2-years. In multivariate analyses for OS, tumor number ( P = 0.004), portal vein tumor thrombus ( P = 0.004), and Barcelona liver cancer staging ( P < 0.001) were found to be significant. For 2-years OS, the degree of AFP remission at 3 months (rAFP_3M) had an AUC of 0.852 (95% CI: 0.758–0.946, P < 0.001), a sensitivity of 85.5%, and a specificity of 82.6% with a cut-off value of 3.7%. MoRAL score at 3 months (MoRAL_3M) had an AUC of 0.814 (95% CI: 0.728–0.900, P = 0.000), a sensitivity of 76.5%, and a specificity of 77.8% with a cut-off value of 111.64. In new multivariate analyses including the above significant factors plus either rAFP_3M or MoRAL_3M, rAFP_3M ( P < 0.001) and MoRAL_3M ( P < 0.001) were found to be independent prognostic factors in each model. This study confirmed the importance of the changed tumor marker after EBRT rather than the baseline value. Dynamic change of AFP and MoRAL score at post-EBRT 3 months could be recommended as potential indicators for clinical outcomes.